Do Consumers Vote with Their Feet in Response to Negative ESG News? Evidence from Foot Traffic to Retail Locations - DUBE, SVENJA; LEE, HYE SEUNG (GRACE); WANG, DANYE (Journal of Accounting Research, 2026)
ABSTRACT We examine whether and, if so, how retail consumers change their shopping in response to firm‐specific negative environmental, social, and governance (ESG) news. Using an event study methodology, we do not find significant changes in consumer foot traffic in response to negative ESG news, on average. However, the average consumer reacts negatively when such news is covered by national or global media outlets, which elevates consumer awareness. In addition, we provide evidence of the heterogeneity in responses to negative ESG news across consumer groups. Consumers in more ESG‐conscious counties, as measured by county ESG preferences, income, education, and political ideology, reduce store visits in response to negative ESG news. In contrast, consumers in the least ESG‐conscious counties increase their visits in response to negative ESG news. These opposing reactions explain the insignificant average consumer response to negative ESG news. Furthermore, the ESG‐conscious consumers' negative reaction is, at most, modest, dissipating within six weeks. Overall, our findings suggest that firms face divergent responses to ESG activities from different consumer groups, underscoring the divisive nature of ESG issues.